Pengembangan Modul Keanekaragaman Pohon Sialang (Koompassia Excelsa) Untuk Bahan Ajar Materi Keanekaragaman Tumbuhan Di Kelas X SMAN Kabupaten Pelalawan Riau - Leni Agustina; Ibnu Hajar (LPPM Politeknik Pratama, 2024)
This research aims to produce a teaching material module on the diversity of Siang trees in Pelalawan Regency, Riau for biology subjects in class X SMAN. This research is a type of development research (Research and Development) with the development of the Plomp 2013 method. The subjects of this research are the people of Pelalawan Regency, Riau and the subjects of the teaching materials are class X students at SMAN Bandar Petalangan, SMAN Bunut, and SMAN Pangkalan Kuras. Research data was obtained from validation sheets assessed by material experts, learning experts, learning media experts, and biology teachers, as well as response questionnaires obtained from the results of limited trials from students. The results of this research show that the quality of the validity of the teaching material module based on validation results by material experts is in the very valid category with an average percentage of 87.69% (very valid), the validation results from learning experts get an average percentage of 91.76% (very valid), validation results from learning media experts got an average percentage of 94% (very valid), and validation results by three biology teachers got an average of 90.44% (very valid), and test results on students got an average of The average percentage is 90.11% (very practical), based on these several categories, it can be concluded that the learning media developed is very valid and can be used as teaching material that can help students' learning process.